2012
DOI: 10.5846/stxb201105230675
|View full text |Cite
|
Sign up to set email alerts
|

Nabkha morphology and sand-fixing capability of four dominantCaraganaspecies in the desert region of the Inner Mongolia Plateau

Abstract: The drought鄄resistant shrubs Caragana korshinskii, Caragana stenophylla, Caragana roborovskyi, and Caragana tibetica, are distributed mainly in the arid and semi鄄arid areas of the Inner Mongolia Plateau, China. They are important plants for fodder resource, and are known as " lifesaving plants冶 to livestock. In addition, they play an important role in fixing sand dunes and conserving water resources. So far, however, very little attention has been paid to the factors determining the sand鄄fixing capability of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies in the grassland of Loess Plateau showed that almost all Caragana seeds were eaten by seed predators within one week of the seeds falling on the ground [42]. However, in sandy land, shrubs can easily be buried by sand, thereby forming nabkhas of various sizes, from 20 to 40 cm in height, under shrub canopies due to wind-deposited sand (Figure 5d) [43]. In this case, Caragana seeds may fall under or next to shrub canopies where they were later buried at various depths in sand together with leaves of shrubs and other debris.…”
Section: Sandy Habitats Facilitate Seed Reproduction Of Shrubsmentioning
confidence: 94%
“…Previous studies in the grassland of Loess Plateau showed that almost all Caragana seeds were eaten by seed predators within one week of the seeds falling on the ground [42]. However, in sandy land, shrubs can easily be buried by sand, thereby forming nabkhas of various sizes, from 20 to 40 cm in height, under shrub canopies due to wind-deposited sand (Figure 5d) [43]. In this case, Caragana seeds may fall under or next to shrub canopies where they were later buried at various depths in sand together with leaves of shrubs and other debris.…”
Section: Sandy Habitats Facilitate Seed Reproduction Of Shrubsmentioning
confidence: 94%